Revitalisasi Batik Jetis Sidoarjo Pada Toko Amri - A Falaqil Isbakhi; Wahyu Eko Pujianto (Universitas 45 Surabaya, 2023)
The purpose of this research is revitalization so that batik is well known by the public and a promotion strategy to increase interest in returning to the community. This research uses a qualitative method which is carried out by gathering information through direct visits or observation, interviews and documentation. In this study, the results were obtained that the way to revive public interest in jetis written batik was by utilizing promotions on existing social media such as Facebook and websites with creative and unique marketing, most likely to attract public interest again by presenting them according to the era. which is currently developing, with this great possibility it will attract back public interest which has begun to fade and the main target is millennials by using social media which they often access.